Histoplasmosis in Israeli Travelers - Segel, Michael J. (Am J Trop Med Hyg, 2015)
Histoplasmosis is a common endemic human mycoses acquired mostly in the Americas. We reviewed 23 cases of histoplasmosis in Israeli travelers; 22 had traveled to Central or South America and one to North America. Fourteen cases had been exposed to bat habitats and were symptomatic, presenting ≤ 3 months after their return. Asymptomatic patients (N = 9) were diagnosed during the evaluation of incidental radiological findings or because a travel partner had been suspected of Histoplasma infection, 16–120 months after their return. Serological testing was positive in 75% of symptomatic cases but only 22% of asymptomatic cases. Histoplasmosis should be considered in travelers returning from the Americas with respiratory or febrile illness within weeks of return, particularly if exposed to bat habitats. Travel history is essential in patients presenting with pulmonary nodules, even years after travel to endemic countries.